2020
DOI: 10.5114/jcb.2020.100378
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of Excel forms based on an automatic calculation of dose equivalent in 2 Gy per fraction in adaptive brachytherapy for cervical cancer

Abstract: Purpose External beam radiotherapy (EBRT) combined with brachytherapy (BT) is the standard mode of radical radiotherapy for locally advanced cervical cancer. The cumulative equivalent doses in 2 Gy per fraction (EQD 2 ) is an important basis for estimating the probability of local control of tumors and monitoring the occurrence of side effects in normal tissues. The purpose of this study was to explore the predictive value of Excel forms based on an automatic calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Cheng et al. reported 119 cervical cancer patients with IGABT, and 38 patients (31.9%) changed the applicator during the course of HDR brachytherapy ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al. reported 119 cervical cancer patients with IGABT, and 38 patients (31.9%) changed the applicator during the course of HDR brachytherapy ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…If the applicator in the previous brachytherapy session is not optimal, a different applicator has to be used in the subsequent fraction(s). Cheng et al reported 119 cervical cancer patients with IGABT, and 38 patients (31.9%) changed the applicator during the course of HDR brachytherapy (37).…”
Section: How Do We Perform 4d Brachytherapy?mentioning
confidence: 99%